2008
DOI: 10.1080/15287390802361755
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Biomonitoring Equivalent (BE) Values for 2,3,7,8-Tetrachlorodibenzo-p-Dioxin (TCDD) and Related Compounds: A Screening Tool for Interpretation of Biomonitoring Data in a Risk Assessment Context

Abstract: Recent efforts by the U.S. Centers for Disease Control and Prevention and other researchers have resulted in a growing database of measured concentrations of dioxins and related compounds in blood samples taken from the general population. However, few tools exist to assist in the interpretation of the measured values in a health risk context. Biomonitoring equivalent (BE) values are defined as the concentration or range of concentrations of a chemical or its metabolite in a biological medium (blood, urine, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…We briefly describe here the method used to develop BE values for the PCDDs/Fs and structurally related PCBs; detailed information is given in Aylward et al, 2008. Several agencies have conducted risk assessments for dioxin-like compounds and have established exposure guidance values in terms of daily, weekly, or monthly intake of these compounds.…”
Section: Development Of Bes For Pcdds/fs and Structurally Related Pcbsmentioning
confidence: 99%
See 2 more Smart Citations
“…We briefly describe here the method used to develop BE values for the PCDDs/Fs and structurally related PCBs; detailed information is given in Aylward et al, 2008. Several agencies have conducted risk assessments for dioxin-like compounds and have established exposure guidance values in terms of daily, weekly, or monthly intake of these compounds.…”
Section: Development Of Bes For Pcdds/fs and Structurally Related Pcbsmentioning
confidence: 99%
“…Biomonitoring equivalents have been estimated corresponding to each of these exposure guidance values (Aylward et al, 2008). Each BE value is derived through consideration of the toxicological data underlying the respective exposure guidance value, understanding of the pharmacokinetics of dioxins in humans, and application of appropriate uncertainty factor components to the toxicological point of departure (Aylward et al, 2008).…”
Section: Development Of Bes For Pcdds/fs and Structurally Related Pcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…BE values are designed to be used as screening tools to assess whether chemicals have a large, a small, or no margin of safety compared to existing health-based exposure guidelines [46]. Aylward et al reported that a serum lipid-adjusted TEQ of approximately 15 pg·g −1 lipid, on the basis of neurodevelopmental effects, is consistent with the minimal risk level (MRL) recommended by the Agency for Toxic Substances and Disease Registry [47]. Referring to the TEQs ∑(PCDDs/Fs + dl-PCBs) in our data, 42.7% of the participants exhibited levels higher than the BE value.…”
Section: Resultsmentioning
confidence: 99%
“…The above systemic TEQ estimates that were calculated using the adjusted systemic TEF values can be further evaluated in a risk assessment context. Previously, Biomonitoring Equivalents (BEs), which are estimates of steady-state biomarker concentrations consistent with chronic exposure at a reference dose (RfD) or tolerable daily intake (TDI), have been estimated for TCDD (Aylward et al 2008 , 2013 ). The physiologically based pharmacokinetic (PBPK) model for TCDD selected by USEPA in their 2012 RfD evaluation was used to estimate steady-state serum TCDD concentrations consistent with chronic exposure at the USEPA reference dose (RfD) or the WHO JECFA TDI.…”
Section: Human Risk Assessment Of Dlcs In Perspectivementioning
confidence: 99%